Development of cookies with fruit co-products (Research, Society and Development, 2020)
The aim of this study was to develop flours produced with fruit by-products and their application in cookies. Six flours were developed: pineapple peel, mango peel, banana peel, orange peel, watermelon rind and mango almond. The standard formulation of the cookie was studied and the others replacing 15% of the wheat flour for each flour produced. Flours were characterized by yield, pH and color parameters, while cookies by specific volume, color, texture and sensory acceptance, being analyzed by Pearson's correlation. The flours showed acid pH and different colors, with the banana skin the darkest and the mango almond the lightest. Flour yield varied between 9.8% (banana peel) and 52.2% (mango almond). The specific volumes of the formulations showed no difference, with a value of 1.69 ± 0.03cm3.g-1 for the standard sample. The hardness varied between 26.22±3.24N (orange peel) and 52.37±4.55N (watermelon skin). The color parameters of the cookies were influenced by the added flours, with the Delta E being greater in that produced with banana peel flour. Cookies had good sensory characteristics in the appearance and taste attributes. In Pearson's correlation, it was possible to observe that the specific volume interferes with the perception of flavor and that they expect a product with a similar appearance to the standard. In this context, there is the possibility of preparing nutritious cookies and with good acceptance from the use of parts usually discarded from fruits.